2021
DOI: 10.1097/md.0000000000027669
|View full text |Cite
|
Sign up to set email alerts
|

DDX10 and BYSL as the potential targets of chondrosarcoma and glioma

Abstract: To provide reliable molecular markers and effective therapeutic targets for chondrosarcoma and glioma.Gene Set Enrichment (GSE) 29745 and GSE48420 were downloaded from the Gene Expression Omnibus (GEO) database. Differently expressed genes (DEGs) were identified by the GEO2R. We annotated the function of common DEGs through Digital Audio/Video Interactive Decoder (DAVID) and Metascape. Protein-protein interaction network construction was performed through STRING. Hub genes were identified by the two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…[12] There have been many studies on DM from chondrosarcoma. For example, DDX10 and BYSL are presumed to be potential targets for chondrosarcoma, [20] in addition to IDH1/2 and COL2A1 as possible therapeutic targets for chondrosarcoma. [21] However, these studies are based on the molecular level and not on clinical features.…”
Section: Discussionmentioning
confidence: 99%
“…[12] There have been many studies on DM from chondrosarcoma. For example, DDX10 and BYSL are presumed to be potential targets for chondrosarcoma, [20] in addition to IDH1/2 and COL2A1 as possible therapeutic targets for chondrosarcoma. [21] However, these studies are based on the molecular level and not on clinical features.…”
Section: Discussionmentioning
confidence: 99%
“…This study was done regarding MIQE recommendation 23. The expression of IGFBP4 and TAGLN was detected by RT-qPCR 18 , 20 . GAPDH was used as the control gene.…”
Section: Methodsmentioning
confidence: 99%
“…Bioinformatics studies biological problems using the methods of applied mathematics, informatics, statistics, and computer science. Some studies have researched the expression profile of RNA in osteosarcoma by using bioinformatics methods and found that bioinformatics analysis might be one valuable tool for the research of osteosarcoma 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Another exciting prospect is to identify SL and SDL partners that have already been implicated in cell apoptosis in a cancer-specific manner or whose DEAD/H-box helicase partners, when overexpressed, have a putative apoptotic nature. An elevated expression of DDX10 in cancer leads to a poor survival rate in chondrosarcoma patients ( 78 ). Additionally, inhibition of α-synuclein displays tumor growth suppression in melanoma cells ( 189 ).…”
Section: Exploiting Dead/h-box Helicases For Synthetic Lethality Appr...mentioning
confidence: 99%